2009
DOI: 10.3126/eco.v15i0.1935
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Coal Smoke Pollution on the Biomass and Chlorophyll Pigments of <i>Brassica juncea</i>

Abstract: The effect of coal smoke pollution on the biomass and chlorophyll pigments of Brassica juncea were studied at 0.5, 2, 4, 6 and 20 km distance leeward from a thermal power plant complex. The root, shoot and total biomass and chlorophyll a, chlorophyll b and total chlorophyll were significantly reduced up to a distance of 4 km from the source of pollution. The data indicates that the degree of response increased with decreasing distance from the source of pollution in comparison to the reference site ‘c' situate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…The lower amount of chlorophyll a, chlorophyll b, total chlorophyll and carotenoids under polluted environment were also noted in several other studies (Singh et al 1985;Singh et al 1990;Malabari et al 1991;Dhir et al 1999;Nighat et al 1999Nighat et al , 2000Saquib, 2008;Iqbal et al 2010;Chauhan and Joshi, 2010). Several researchers have reported reduced carotenoid content under air pollution (Joshi et al, 2009;Tiwari et al, 2006…”
Section: Comparison Between the Meanssupporting
confidence: 71%
“…The lower amount of chlorophyll a, chlorophyll b, total chlorophyll and carotenoids under polluted environment were also noted in several other studies (Singh et al 1985;Singh et al 1990;Malabari et al 1991;Dhir et al 1999;Nighat et al 1999Nighat et al , 2000Saquib, 2008;Iqbal et al 2010;Chauhan and Joshi, 2010). Several researchers have reported reduced carotenoid content under air pollution (Joshi et al, 2009;Tiwari et al, 2006…”
Section: Comparison Between the Meanssupporting
confidence: 71%
“…It was found at rural site in Varanasi, experiencing low concentrations of SO 2 7.3 ppb and NO 2 14.5 ppb and high O 3 concentration (35 ppb) found 10 and 14 % reduction in yield of rice cultivars NDR 97 and Saurabh 950 grown at ambient air (Rai and Agrawal, 2008). As per Saquib (2008), it was observed that the biomass and chlorophyll pigment of Brassica juncea has altered due to coal-smoke pollution.…”
Section: Crops Vegetables and Trees Damage By Air Pollutionmentioning
confidence: 81%